Arthroscopic Resection of Intra-Articular Osteochondromas of the Hip - Thiago Aguiar, M.D.; Pedro Dantas, M.D. (Arthroscopy Techniques, 2014)
Proximal femur osteochondromas are relatively rare, particularly in the femoral neck. The choice of treatment poses difficulties to the surgeon. We report an unusual case of a patient with 2 osteochondromas in the femoral neck causing femoroacetabular impingement. Appropriate identification and precise resection of the lesions are important steps of the surgical procedure. We present our arthroscopic surgical technique to access the lesions and perform their resection. To our knowledge, this is the first report of hip arthroscopic resection of 2 osteochondromas with considerable dimensions causing femoroacetabular impingement.